Adenosarcoma of the uterine cervix – a novel case report and review of the literature - Maciejewska, Oliwia; Wilczynski, Milosz; Romanowicz, Hanna; Malinowski, Andrzej (Menopause Review/Przegląd Menopauzalny, 2025)
Adenosarcomas constitute approximately 1% of all malignancies affecting the female reproductive system. Their most common locations are the uterine corpus and ovaries. Cervical adenosarcomas are rare and poorly described in the literature. Therefore, there are still no treatment guidelines for such cases, and the proper scope of the surgical procedure has become questionable. The most popular options include total abdominal hysterectomy and/or bilateral salpingo-oophorectomy (BSO). Generally, the prognosis is relatively good, among other things, because it is detected in the earlier International Federation of Gynaecology and Obstetrics stage than other locations, with a 5-year overall survival rate of 63–84%. Here, the present paper describes the case of a 44-year-old female with adenosarcoma located in the cervix. The patient experienced abnormal vaginal bleeding occurring 7–10 days before proper menstruation and pelvic pain. Interestingly, despite a normal routine Pap smear test, the cervical mass was revealed in transvaginal ultrasonography. A subsequent biopsy of the lesion confirmed the presence of low-grade adenosarcoma. A radical hysterectomy (RH) with BSO and pelvic lymph node sampling was performed. The patient reports resolution of all symptoms. Our case study highlights the effectiveness of RH as the mainstay treatment for cervical adenosarcomas. Furthermore, we discuss these tumours’ pathology and imaging features, as well as other therapeutic options. The present study has an exceptional value for practicing gynaecologists and oncologists.